Effect of Helium Cold Plasma on the Moisture Sorption Isotherms of Milled Rice - CAO Zi-yi; LI Xing-jun; SONG Hong-dong; ZHAO Ming-hui (Liang you shipin ke-ji, 2023)
The low-pressure radio-frequency (RF) cold plasma equipment has been developing in China for over 20 years. This equipment can significantly shorten rice cooking time and increase the solid solubility in the porridge. The safety evaluation of cold plasma technology in food industry is being carried out during the recent five years. This study measured the moisture desorption/adsorption isotherms of milled rice treated zero to four times by 120 W-20 s helium cold plasma (CP, 140 Pa, 13.56 MHz, the distance from plasma resource to the samples is 3 cm, 300 g samples were treated each time). In the range of 5 to 45 ℃ and 10% to 90% RH, in contrast to the untreated samples, CP repeat treatments did not change the hygroscopic properties such as monolayer and multilayer moisture properties and the moisture content of safe storage, but they increased hydrophilicity and water absorption rate of milled rice with a significant decrease in water contract angle. This study gives basic data for the safe storage of CP-treated milled rice.